Adding a new dimension to teaching and learning in sri lankan schools - Ekanayake, S.Y.; Sethunga, P. (University of Jaffna, 2012)
This research study was motivated by previous research which found that the use of mobile phones could enhance the effectiveness of teaching and learning. The aim of this paper is to present the findings of three secondary level science lesson implementations in which the mobile phones were integrated in teaching and learning processes. A group of secondary level science teachers developed these lessons as small groups. The study used qualitative approach and data were collected using observation via video, audio recording and written materials. Then they were analyzed using Thematic Analysis with the support of NVivo8 qualitative data analysis software. Four themes were derived as ‘mobile phones supported to bring the outside world into the classroom’, ‘mobile phones supported to enhance students’ engagement in science teaching and learning’, ‘mobile phones supported to share information’ and ‘mobile phones supported to assess students’ science learning and behaviour’. The findings show that the integration of mobile phones in science lessons helped to get students’ attention towards the lesson, provided more opportunities to students’ active participation, connected students’ science learning with their home environment as well as their school garden and provided more opportunities to assess students’ learning during and after the lessons. Therefore, mobile phones have the potential to add a new dimension to science teaching and learning and enhance the effectiveness of it.
Keywords: Science Lesson; Science Learning; Inegration of Mobile Phones in Lessons